Improvement of diffusion weighted MRI by practical B0 homogenization for head & neck cancer patients undergoing radiation therapy. (May 2022) - Bielak, Lars; Henrik Nicolay, Nils; Ludwig, Ute; Lottner, Thomas; Rühle, Alexander; Grosu, Anca-Ligia; Bock, Michael
Highlights: Evaluation of improvement in diffusion imaging in head and neck cancer. Quantification with respect to Nyquist ghost artifact. Water bags as simple, accessible tool to improve MR image quality. Use of quantitative MRI in radiation therapy planning. Abstract: Background: MRI is a frequently used tool in radiation therapy planning. For MR-based tumor segmentation, diffusion weighted imaging plays a major role, which can fail due to excessive image artifacts for head and neck cancer imaging. Here, an easy-to-use setup is presented for imaging of head and neck cancer patients in a radiotherapy thermoplastic fixation mask. Methods: In a prospective head and neck cancer study, MRI data of 29 patients has been acquired at 3 different time points during radiation treatment. The data was analyzed with respect to Nyquist ghosting artifacts in the diffusion images in conventional single shot and readout segmented EPI sequences. For 9 patients, an improved setup with water bags for B0 homogenization was used, and the impact on artifact frequency was analyzed. Additionally, volunteer measurements with B0 fieldmaps are presented. Results: The placement of water bags to the sides of the head during MRI measurements significantly reduces artefacts in diffusion MRI. The number of artifact-free images in readout segmented EPI increased from 74% to 95% of the cases. Volunteer measurements showed a significant increase in B0 homogeneity across slices (head foot direction) as well as within each slice. Conclusions: The placement of water bags for B0 homogenization is easy to implement, cost-efficient and does not impact patient comfort. Therefore, if very sophisticated soft- or hardware solutions are not present at a given site, or cannot be implemented due to restrictions from the thermoplastic mask, this is an excellent alternative to reduce artifacts in diffusion weighted imaging.